2022
DOI: 10.1101/2022.05.26.493577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Landscape scale ecology of Tetracladium spp. fungal root endophytes

Abstract: BackgroundThe genus Tetracladium has been traditionally regarded as an Ingoldian fungus or aquatic hyphomycete – a group of phylogenetically diverse, polyphyletic fungi which grow on decaying leaves and plant litter in streams. Recent sequencing evidence has shown that Tetracladium spp. may also exist as root endophytes in terrestrial environments, and furthermore may have beneficial effects on the health and growth of their host. However, the diversity of Tetracladium spp. communities in terrestrial systems a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…The results of the present study, obtained in SDS-PAGE and western blot, confirmed the presence of Cu/Zn SOD in the liver and in the small and large intestines at 12 h and 7 days after hatching in all experimental groups and the control. Additional analysis of polyacrylamide gels using GelAnalyzer 19.1 [52] software showed the highest expression of Cu/Zn SOD in the small and large intestine at 12 h post-hatch in the groups of birds receiving the multi-strain probiotic and Zn-Gly chelate (group IV) or Zn-Gly chelate (group III). At 7 days of age, however, the highest expression of Cu/Zn SOD was noted in the small intestine in group IV, receiving the multi-strain probiotic and Zn-Gly chelate, and in the large intestine in group III, receiving Zn-Gly chelate.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study, obtained in SDS-PAGE and western blot, confirmed the presence of Cu/Zn SOD in the liver and in the small and large intestines at 12 h and 7 days after hatching in all experimental groups and the control. Additional analysis of polyacrylamide gels using GelAnalyzer 19.1 [52] software showed the highest expression of Cu/Zn SOD in the small and large intestine at 12 h post-hatch in the groups of birds receiving the multi-strain probiotic and Zn-Gly chelate (group IV) or Zn-Gly chelate (group III). At 7 days of age, however, the highest expression of Cu/Zn SOD was noted in the small intestine in group IV, receiving the multi-strain probiotic and Zn-Gly chelate, and in the large intestine in group III, receiving Zn-Gly chelate.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the polyacrylamide gel photographs, amplicon size was measured using the software, GelAnalyzer 19.1 (Lazar and Lazar 2019). The SSR primers were evaluated based on amplification success, as well as the number and sizes of each amplicon.…”
Section: Discussionmentioning
confidence: 99%